Comparison between rectal and body surface temperature in dogs by the calibrated infrared thermometer. (June 2020) - Cugmas, Blaž; Šušterič, Primož; Gorenjec, Nina Ružić; Plavec, Tanja
Highlights: Dogs poorly tolerate rectal temperature measurements with a contact thermometer. Existing alternative approaches used uncalibrated infrared thermometers. Gum and inguinal temperature are correlated moderately to rectal temperature. Hyperthermia was detected with sensitivity and specificity up to 90.0% and 78.6%. Future studies should include a calibrated thermometer and control external factors. Abstract: Because dogs tolerate conventional rectal temperature measurements poorly, a calibrated infrared thermometer was tested for assessing canine body surface temperature. Body surface temperature of 204 dogs was estimated on various sites (digit, snout, axilla, eye, gum, inguinal region, and anal verge). Having rectal temperature as the gold standard, temperature difference, Spearman's correlation coefficient, hyperthermia and hypothermia detection sensitivity and specificity, and stress response score was calculated for each measurement site. Although the canine body surface temperature was considerably lower than the rectal temperature, there was a moderate correlation between both temperatures. Spearman's coefficients were 0.60 ( p < 0.001) for the inguinal region with a single operator and 0.50 ( p < 0.001) for the gum with multiple operators. Measurement site on the gum additionally guaranteed hyperthermia detection sensitivity and specificity up to 90.0% (95% CI: [66.7 100]) and 78.6% (95% CI: [71.6 85.2]), respectively. Measurements with the infrared thermometer provoked a statistically significant lower stress response (mean stress scores between 1.89 and 2.48/5) compared to the contact rectal measurements (stress score of 3.06/5). To conclude, the correct body surface temperature measurement should include a calibrated thermometer, reliable sampling, and the control of external factors such as ambient temperature influence. The transformation of body surface temperature to the recognized rectal temperature interval allows more straightforward data interpretation. The gum temperature exhibited the best clinical potential since the differences to rectal temperatures were below 1°C, and hyperthermia was detected with the sensitivity of up to 90%.